Nitric oxide is involved in growth regulation and re-orientation of pollen tubes - Prado, AM (2004)
Nitric oxide (NO) controls diverse functions in many cells and organs of animals. It is also produced in plants and has a variety of effects, but little is known about their underlying mechanisms. In the present study, we have discovered a role for NO in the regulation of pollen tube growth, a fast tip-growing cellular system. Pollen tubes must be precisely oriented inside the anatomically complex female ovary in order to deliver sperm. We hypothesized that NO could play a role in this guidance and tested this hypothesis by challenging the growth of pollen tubes with an external NO point source. When a critical concentration was sensed, the growth rate was reduced and the growth axis underwent a subsequent sharp reorientation, after which normal growth was attained. This response was abrogated in the presence of the NO scavenger CPTIO and affected by drugs interfering in the cGMP signaling pathway. The sensitivity threshold of the response was significantly augmented by sildenafil citrate (SC), an inhibitor of cGMP-specific phosphodiesterases in animals. NO distribution inside pollen tubes was investigated using DAF2-DA and was shown to occur mostly in peroxisomes. Peroxisomes are normally excluded from the tip of pollen tubes and little if any NO is found in the cytosol of that region. Our data indicate that the rate and orientation of pollen tube growth is regulated by NO levels at the pollen tube tip and suggest that this NO function is mediated by cGMP.